The effect of a reaction training system based on sonsic reaction training on improving the agility of beginner badminton athletes in China - Tiara Mahsela; Dikdik Zafar Sidik; Geraldi Novian; Wang Huai Yu (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
Agility is a crucial element in the movement performance of badminton players, as it requires the ability to make quick decisions to produce accurate motor responses. However, evidence regarding technology-assisted reaction training programs specifically designed to improve agility in beginner badminton athletes remains limited. The participants were 22 beginner badminton players aged 8–12 years from Tacheng, China, recruited through purposive sampling and divided into an experimental group (EG, n = 11) and a control group (CG, n = 11). The experimental group participated in an eight-week agility training program using the Sonic Reaction Training System twice a week for approximately two hours per session, while the control group continued their regular training program without the reaction-based intervention. the Six-Point Shuttle Run Test, a standardized field test that assesses multidirectional agility through repeated changes of direction before and after the intervention. The data were then analyzed using Shapiro–Wilk normality test, Levene's test for homogeneity, paired-samples t-tests, independent-samples t-tests, and Cohen's d effect size analysis to compare changes in agility performance between the two groups. The experimental group demonstrated a statistically significant change (t = 2.850, p = 0.017); however, the mean agility score decreased from 17.67 ± 3.23 at pretest to 15.98 ± 2.97 at posttest. In contrast, the control group showed a significant improvement, with the mean score increasing from 17.49 ± 4.52 to 20.42 ± 4.12 (t = −4.621, p = 0.001). Furthermore, a significant difference was observed between groups at posttest (t = −2.904, p = 0.009). These findings indicate that, under the conditions of the present study, the Sonic Reaction Training System did not produce the expected improvement in agility performance among beginner badminton players. Future studies should employ larger sample sizes, report effect sizes and statistical power, and optimize training protocols to further evaluate the effectiveness of technology-assisted reaction training.